Evaluation of Social Interventions with People with Disabilities: A Systematic Literature Review. - Mira-Aladrén, Marta; Martín-Peña, Javier; Gil-Lacruz, Marta (Social Work Research, 2024)
This article aims to review the scientific production on social interventions (SI) in the field of persons with disabilities (PWD) and their families and to analyze its evaluations. To do so, it starts from the context of the social model of care of the United Nation's Convention on the Rights of Persons with Disabilities and the sustainable development goals, and the evaluation of SI. The methodology proposes a systematic review of the existing literature on SI with PWD and their evaluation, based on the preferred reporting items for systematic review and meta-analysis (or PRISMA) model, including 19 articles. The results highlight issues such as the scarcity of publications with evaluations, the lack of homogeneity in the evaluation indicators used, the large number of interventions related to intellectual disability, and a large proportion of community interventions. This scoping review assists future research to consider different questions about evaluation indicators and implementation of the social model or social inclusion, among others.